UJI AKTIVITAS EKSTRAK ETIL ASETAT DAUN KAYU JAWA (Lannea coromandelic (Houtt.) Merr.) TERHADAP PENYEMBUHAN LUKA BAKAR PADA TIKUS PUTIH (Rattus norvegicus) - Bayu Putra; Safriani Rahman (As-Syifaa Jurnal Farmasi, 2020)
Wound healing is a process of repairing skin and soft tissue when these organs are injured. One of the plants that are presumed to affect wound healing is Kayu Jawa (Lannea coromandelic (Houtt.) Merr.). This research aims to determine the healing effect of burns and the effective dose of ethyl acetate extract of Kayu Jawa’s leaves. The animal test that has been induced using a hot plate with temperature 100oC stuck at the back of mice were divided into 5 (five) groups. Group 1 Na.CMC as Negative control, Group 2 Lanakeloid-E as Positive control, Group III, IV, and V were extract ethyl acetate of Kayu Jawa’s leaves (Lannea coromandelic (Houtt.) Merr) with 3 dosage variations namely, 75 mg/kg, 150 mg/kg, and 300 mg/kg were given topically 2 times a day for 21 days. Then wound area measure using calipers. The group with 300 mg/kg dosage has the best effect for reducing wound area of burns, with statistical value not significantly different from the comparison group (Lanakeloid-E) with a percentage value of 84%.